Impression of Information Technology and Binary in Businesses - Baub S*1; Dey T2 (AlQalam Journal of Medical and Applied Sciences, 2020)
The advances in information and communication technology over the past few years have no excuse. And with that comes the certainty that this development will continue and be so strong that technology will be in all branches of the world. Thanks to information technology, people’s lives have become much easier, simpler and more comfortable. It is now very easy to travel around the world from home, marketing, banking, various services or the virtual world. That is why now there is no work of man where technology has not touched. In the face of the challenges of the 21st century, information and communication technology has opened the door to endless possibilities for the world’s poor. In the continuity of history, after the agrarian revolution, the industrial revolution, the present world is going to face a new revolution called information revolution. The main purpose of this paper is to explain to people how information and communication technology is related to us and business and to present the strategic aspects of information and technology and also to present how to select a product using binary.